(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the characteristics and advantages of Bloom’s taxonomy in elementary school students and the essence of all the reforms that are currently being implemented in the field of education are related to one thing, that is, to improve the quality of education, less effort in the teaching process. aimed at achieving greater efficiency by spending. In today’s society, the relevance of developing children’s creative activity from elementary school age, the pedagogical possibilities and importance of teaching primary school students to creative activities, and the effectiveness of organizing students’ creative abilities based on modern educational approaches are described.